2008
DOI: 10.1021/es702205u
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Sorption Properties of Cutin and Cutan Biopolymers

Abstract: Plant cuticles have been reported as highly efficient sorbents for organic compounds. The objective of this study was to elucidate the sorption and desorption behavior of polar and nonpolar organic compounds with the major structural components of the plant cuticle: the biopolymers cutin and cutan. The sorption affinity values of the studied compounds followed the order: phenanthrene > atrazine > chlorotoluron > carbamazepine. A higher sorption affinity of phenanthrene and atrazine to cutin was probably due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
(90 reference statements)
2
23
1
Order By: Relevance
“…4), indicating that the polarity of the SOM fractions has a significant effect on the sorption capacity of atrazine. It has also been reported that higher-polarity biopolymers have a higher sorption affinity for atrazine (Shechter and Chefetz 2008), and atrazine sorption by humic substances exhibited a positive correlation with the substances' polar carbon contents (Wang et al 2011). However, this result differs from the previous reports on the sorption of apolar HOCs such as phenanthrene and lindance by fractionated SOM, which described a negative relationship between SOM polarity and logK OC (Kang and Xing 2005;Wang et al 2011).…”
Section: Effects Of Fractionated Som Properties On Atrazine Sorptioncontrasting
confidence: 55%
“…4), indicating that the polarity of the SOM fractions has a significant effect on the sorption capacity of atrazine. It has also been reported that higher-polarity biopolymers have a higher sorption affinity for atrazine (Shechter and Chefetz 2008), and atrazine sorption by humic substances exhibited a positive correlation with the substances' polar carbon contents (Wang et al 2011). However, this result differs from the previous reports on the sorption of apolar HOCs such as phenanthrene and lindance by fractionated SOM, which described a negative relationship between SOM polarity and logK OC (Kang and Xing 2005;Wang et al 2011).…”
Section: Effects Of Fractionated Som Properties On Atrazine Sorptioncontrasting
confidence: 55%
“…The peaks are assigned to carbonyl stretching associated with free carboxyl, H-bond carboxyl and ester bonds, respectively (Heredia-Guerrero et al, 2010). The peak at 1731 cm −1 was clearly observed in the cutin biopolymer that was used to isolate the studied monomers (Shechter and Chefetz, 2008). The spectrum of the cutin monomers exhibited a shoulder at wavenumber 1731 cm −1 , whereas this peak is clearly observed in the spectra of all montmorillonitemonomer complexes.…”
Section: Esterification Of Cutin Monomers On Montmorillonite Surfacesmentioning
confidence: 96%
“…Monomers of cutin were isolated from tomato (Lycopersicon esculentum) fruit cuticle using the previously reported method (Shechter and Chefetz, 2008). Briefly, tomato fruit peels were treated with oxalic acid and ammonium oxalate solution to remove noncuticular matter.…”
Section: Isolation Of Cutin Monomersmentioning
confidence: 99%
“…Cuticular waxes were isolated from the leaves of Agave americana as described in Shechter and Chefetz (2008). Waxes were extracted from manually peeled cuticular sheets by Soxhlet extraction with chloroform/methanol (1:1 v/v) for 6 h. The solvent was evaporated at 40°C under vacuum, and waxes were freeze-dried, ground and sieved.…”
Section: Isolation Of Waxes and Extraction Of Hamentioning
confidence: 99%
“…The outer surface of the cuticle is covered with waxes, which consist of a complex mixture of long-chain aliphatic and cyclic components in crystalline and amorphous phases (Santier and Chamel, 1998;Chen and Xing, 2005). A number of reports have demonstrated that cuticular materials are efficient natural sorbents for hydrophobic organic compounds (HOCs) (Chefetz et al, 2000;2003;Shechter and Chefetz, 2008).…”
Section: Introductionmentioning
confidence: 99%